2013
DOI: 10.1074/mcp.m113.028324
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveals That Tumor Xenografts Induce Liver Dysfunction

Abstract: Metabolomics, based on ultraperformance liquid chromatography coupled with electrospray ionization quadrupole mass spectrometry, was used to explore metabolic signatures of tumor growth in mice. Urine samples were collected from control mice and mice injected with squamous cell carcinoma (SCCVII) tumor cells. When tumors reached ϳ2 cm, all mice were killed and blood and liver samples collected. The urine metabolites hexanoylglycine, nicotinamide 1-oxide, and 11␤,20␣-dihydroxy-3-oxopregn-4-en-21-oic acid were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…//serum ↑(in prediagnosed serum) [89] Xanthine (HMDB00292) GC/MS, UPLC/MS-MS Clinical/ Hepatocellular carcinoma (HCC) arising from hepatitis C (HCV); HCC, hepatitis C cirrhosis, disease controls (DC) and healthy volunteers //serum ↑ (HCC vs DC) [88] GC-TOF Clinical/Adenocarcinoma a type of non-small-cell lung cancer (NSCLC) // tissue [94] NMTR Animal /rat model of gastric carcinogenesis//serum [102] GC-MS and LC-MS/MS Clinical / normal ovarian tissue vs. primary epithelial ovarian cancer (EOC) vs. metastatic tumors resulting from primary ovarian cancer (MOC)// tissue ↑EOC [86] Lauric acid (HMDB00638) GC-MS Clinical/melanoma Pilot study (small cohort)- //biopsied tissue melanoma and matched control non-neoplastic skin from the same patient (VOC) [103] Alkanes such as ethane and pentane GC-MS Review breath cancer/in vivo vs. in vitro hypoxic and hyperoxic cond// Volatile organic compounds (VOC) [104] Aldehydes, alcohols and ketones GC-MS Review breath cancer/in vivo vs. in vitro hypoxic and hyperoxic cond// Volatile organic compounds (VOC) [104] Indoxyl sulfate (HMDB00682) LC-MS Clinical/epithelial ovarian cancer (EOC) primary EOC vs post-operative EOC patients vs recurrent EOC//plasma samples ↑ (post operative)↓(relapsed) [95] H NMR Clinical/Esophageal adenocarcinoma (EAC) Barrett’s esophagus and EAC, // urine ↑ (EAC) [85] Asymmetric dimethylarginine (HMDB01539) UPLC-ESI-QTOF/MS Animal /rodent squamous cell carcinoma (SCCVII) injected into the subcutaneous space of female C3H/Hen mice temporal study//. serum, liver, and tumor [105] 24-nor−5 β -cholane-triol (NA) UPLC–MS Animal /Dicer-Pten double knockout (DKO) mice. Simulates High-grade serous carcinoma (HGSC) in women – early tumor (ET) //...…”
Section: Metabolomics Insights Into Redox State Of Cancermentioning
confidence: 99%
“…//serum ↑(in prediagnosed serum) [89] Xanthine (HMDB00292) GC/MS, UPLC/MS-MS Clinical/ Hepatocellular carcinoma (HCC) arising from hepatitis C (HCV); HCC, hepatitis C cirrhosis, disease controls (DC) and healthy volunteers //serum ↑ (HCC vs DC) [88] GC-TOF Clinical/Adenocarcinoma a type of non-small-cell lung cancer (NSCLC) // tissue [94] NMTR Animal /rat model of gastric carcinogenesis//serum [102] GC-MS and LC-MS/MS Clinical / normal ovarian tissue vs. primary epithelial ovarian cancer (EOC) vs. metastatic tumors resulting from primary ovarian cancer (MOC)// tissue ↑EOC [86] Lauric acid (HMDB00638) GC-MS Clinical/melanoma Pilot study (small cohort)- //biopsied tissue melanoma and matched control non-neoplastic skin from the same patient (VOC) [103] Alkanes such as ethane and pentane GC-MS Review breath cancer/in vivo vs. in vitro hypoxic and hyperoxic cond// Volatile organic compounds (VOC) [104] Aldehydes, alcohols and ketones GC-MS Review breath cancer/in vivo vs. in vitro hypoxic and hyperoxic cond// Volatile organic compounds (VOC) [104] Indoxyl sulfate (HMDB00682) LC-MS Clinical/epithelial ovarian cancer (EOC) primary EOC vs post-operative EOC patients vs recurrent EOC//plasma samples ↑ (post operative)↓(relapsed) [95] H NMR Clinical/Esophageal adenocarcinoma (EAC) Barrett’s esophagus and EAC, // urine ↑ (EAC) [85] Asymmetric dimethylarginine (HMDB01539) UPLC-ESI-QTOF/MS Animal /rodent squamous cell carcinoma (SCCVII) injected into the subcutaneous space of female C3H/Hen mice temporal study//. serum, liver, and tumor [105] 24-nor−5 β -cholane-triol (NA) UPLC–MS Animal /Dicer-Pten double knockout (DKO) mice. Simulates High-grade serous carcinoma (HGSC) in women – early tumor (ET) //...…”
Section: Metabolomics Insights Into Redox State Of Cancermentioning
confidence: 99%
“…Lipidomics is a sub-metabolomics platform that provides a comprehensive analysis of lipid species within a cell or tissue, which plays an essential role in defining the biochemical mechanisms of lipid-related disease processes through identifying alterations in cellular lipid metabolism, trafficking and homeostasis [42, 43]. The current study of metabolomics and lipidomics profiling of CYP7A1-tg mice using ultra-performance liquid chromatography-coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (UPLC-ESI-QTOFMS) detected and characterized small organic molecules in biological materials [4447]. This study explores the involvement of metabolites such as phospholipids and bile acids in the regulation of metabolic homeostasis, and provides insights into the mechanism for the anti-obesity and anti-diabetic effect of increased bile acid pool and altered bile acid composition.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry-based metabolomics has become a powerful tool for the characterization of metabolites in biological matrices and has been applied to studies in hepatology. Notably, metabolomic data for nonalcoholic steatohepatitis (5), cholestasis (6), viral hepatitis (7), liver dysfunction (8,9), and hepatocellular carcinoma (10) have been obtained in the recent years. These studies revealed that metabolic disorders involving BAs and phospholipids are a core phenotype for hepatobiliary diseases (5,10,11).…”
mentioning
confidence: 99%